التدخل الدولي ومساهمته في إسقاط الدولة في ليبيا والإطاحة بنظام معمر القذافي = International intervention and its contribution in the overthrow of the Libyan State and the overthrow of the regime of Muammar Gaddafi - EL buseifi, Saleh .S. Masoud; Abdel Salam, El Fatih Abdullahi (Al-Hikmah, 2020)
تتناول هذه الدراسة أحداث التدخل الدولي في ليبيا عام 2011م، وأسقاط الدولة في ليبيا والإطاحة بنظام حكم معمر القذافي، الذي شكل دولة مركزية قوية استطاع بسط نفوذه على سائر تراب الوطن بقبضة أمنية حديدية لفترة زمنية طويلة، وكان له حضور على المستوى الإقليمي والدولي، وتم تصنيف الحكم في ليبيا من ضمن دول محور الشر في الاستراتيجية الأمريكية، حيث تبلورت شخصية العقيد معمر القذافي كقائد معاد للغرب، إضافة إلى الخلافات والعداءات مع الدول المجاورة، لذلك ادخل النظام الليبي في عهد القذافي ليبيا في زوبعة من المشاكل، وبخاصة مع الدول الأجنبية، حتى أضحى الاغتيال الاقتصادي للأمم أحد أهداف التدخل الأجنبي، وقد استغلت الدول الغربية الأحداث التي عرفتها العديد من الدول العربية، فيما يعرف بالربيع العربي بتصفية حساباتها مع نظام الحكم في ليبيا القذافي، استخدم الباحث المنهج التاريخي لسرد الأحداث الدولية من مرتكزات فكرية بغية فهم واستيعاب تلك التطورات، ومدى تأثير التدخل الدولي في إدخال ليبيا في حالة من الفوضى، وكذلك المنهج الوصفي التحليلي الذي يقوم على أساس وصف دقيق للأحداث الدولية التي تحيط بليبيا، وخاصة فيما يتعلق بإسقاط ليبيا والإطاحة نظام حكم قائم، وإدخال البلاد في مستنقعات العنف المسلح والحروب لتشريد شعبها ونهب ثروات البلاد، وتناول البحث الدوافع المعلنة وغير المعلنة للعديد من القوى الإقليمية والدولية للتدخل في ليبيا، حيث اتضح أن معظم هذه الدوافع لم تخلو من أغراض اقتصادية وجيو استراتيجية. ****************************************************************************** This study deals with the events of international intervention in Libya in 2011 led Culminating in the overthrow of the regime of Muammar Gaddafi, which formed a strong central state that was able to extend its influence over the entire country with an iron security grip for a long time, and had a presence at the regional and international level, and that led to classify governance in Libya as among the axis of evil in the American strategy, where the character of Colonel Muammar Gaddafi crystallized as an antiWestern leader. In addition, to that there were differences and hostilities with neighboring countries, so the Libyan regime under Gaddafi entered Libya in a whirlwind of problems, especially with foreign countries. Western countries have taken advantage of the events that many Arab countries have known during the so-called Arab Spring by settling their scores with Libya's Gaddafi regime. The researcher used the historical method to follow international events in order to understand and absorb these developments. International intervention threw Libya into chaos. The study used as well a descriptive and analytical approach based on a thorough description of the international events surrounding Libya, especially with regard to the overthrow of the existing regime, and the inclusion of the country in the swamps of armed violence and wars to displace the people, the looting of the country's wealth, and touched on the motives declared and undeclared by many of the regional and international powers to intervene in Libya It turned out that most of these motives were not devoid of economic and geostrategic motives.